2023
DOI: 10.3390/eng4030102
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Vibration Monitoring Techniques for Predictive Maintenance of Rotating Machinery

Abstract: Machine failure in modern industry leads to lost production and reduced competitiveness. Maintenance costs represent between 15% and 60% of the manufacturing cost of the final product, and in heavy industry, these costs can be as high as 50% of the total production cost. Predictive maintenance is an efficient technique to avoid unexpected maintenance stops during production in industry. Vibration measurement is the main non-invasive method for locating and predicting faults in rotating machine components. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Data collected by sensors which record oscillations or motions within a structure or system is known as vibration data. It collects information that is important in evaluating the condition [32] and functionality of machinery or systems, such as vibration patterns, amplitude, and frequency. Vibration sensors monitor the intensity and frequency of vibrations in industrial components with unusual patterns indicating possible mechanical problems such as imbalances [9,33], wear [9,25,27,[34][35][36][37] or misalignment [9,[38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected by sensors which record oscillations or motions within a structure or system is known as vibration data. It collects information that is important in evaluating the condition [32] and functionality of machinery or systems, such as vibration patterns, amplitude, and frequency. Vibration sensors monitor the intensity and frequency of vibrations in industrial components with unusual patterns indicating possible mechanical problems such as imbalances [9,33], wear [9,25,27,[34][35][36][37] or misalignment [9,[38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are used to process vibration data obtained from heavy machinery for doing condition monitoring [32]. Some methods use the Fast Fourier Transform (FFT) analysis to highlight frequencies associated with anomalies or problems in the machinery by converting vibration signals from the time domain to the frequency domain [46].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has also been reported [20] that NP strain sensors have the potential to detect acoustic vibrations with an infinitesimal amplitude, which extends the application field of NP arrays towards precision devices with ultrafast dynamics. This possibility opens the way to exploit NP strain sensors as vibration sensors, which are of interest in various application fields ranging from voice recognition [21] to condition-based monitoring (CbM) of machines, which can enable cost savings on machine life and maintenance [22]. A recent review on the use of strain sensors for vibration sensing suggested that resistive strain sensors have a potential that needs to be further investigated, due mainly to Furthermore, it has also been reported [20] that NP strain sensors have the potential to detect acoustic vibrations with an infinitesimal amplitude, which extends the application field of NP arrays towards precision devices with ultrafast dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on the use of strain sensors for vibration sensing suggested that resistive strain sensors have a potential that needs to be further investigated, due mainly to Furthermore, it has also been reported [20] that NP strain sensors have the potential to detect acoustic vibrations with an infinitesimal amplitude, which extends the application field of NP arrays towards precision devices with ultrafast dynamics. This possibility opens the way to exploit NP strain sensors as vibration sensors, which are of interest in various application fields ranging from voice recognition [21] to condition-based monitoring (CbM) of machines, which can enable cost savings on machine life and maintenance [22]. A recent review on the use of strain sensors for vibration sensing suggested that resistive strain sensors have a potential that needs to be further investigated, due mainly to their low cost and low weight, especially when compared to accelerometers, which are currently the industry standard for vibration sensing and monitoring [23].…”
Section: Introductionmentioning
confidence: 99%
“…In [4], a comprehensive review is presented on signal processing techniques for vibration-based feature extraction in structural health monitoring (SHM). The work in [5] addresses the application of vibration-based condition monitoring techniques for the PdM of rotating Machinery. It provides a comprehensive review of vibration data acquisition and analysis, as well as the methods used for fault interpretation and diagnosis, including data acquisition, data transmission, signal processing, and fault detection.…”
Section: Introductionmentioning
confidence: 99%